Relationship between Earnings Quality and Stock Return - Mohsen Khoshtinat; Sbahpoor Esmaeeli (مطالعات تجربی حسابداری مالی, 2005)
This research undertakes the relationship between earnings quality and stock return of the listed companies in the Tehran Stock Exchange. The aim of this research is to assess whether the investors, analysts, and etc. have comprehend the quality of the accountancy information (earnings quality) and utilize it in their decision making process? In order to find the answer to this question we need to take in to account the market reaction. We can assess and evaluate the market reaction with the use of the accumulated data published and in the following two ways: 1-     Volume of transactions 2-     Share price and subsequently the stock return Therefore in this research stock return is an independent variable. Within the earnings quality assessment criteria, two criteria, the ratio between cash flows resulted from operational activities with operational earning and accruals , are selected and their influence on stock return of listed  companies in the Tehran  Stock Exchange are  examined. This research considers four hypotheses. In these hypotheses earnings quality, accruals, discretionary and nondiscretionary accruals are considered as independent variables and stock return as dependent variable. The examination of the research hypotheses, with the help of regression analysis during the period of 1379-1383 (Iranian calendar year), shows that there is little influence between earnings quality and stock returns.